Efficacy of a novel strategy for poststernotomy deep sternal infection after thoracic aorta replacement using a prosthetic graft. Issue 5 (May 2018) - Kuriyama, Motone; Yoshida, Yukitaka; Ninomiya, Hitoshi; Yamamoto, Shin; Sasaguri, Shiro; Akita, Shinsuke; Mitsukawa, Nobuyuki
Summary: Background: Poststernotomy deep sternal wound infections are persistent and occasionally fatal, especially in cases involving prosthetic grafts, because of their complicated structure and virtual impossibility of removal. We aimed to verify the influence of cooperation with plastic surgeons and our novel strategy for treating deep sternal wound infection after aortic replacement on cardiovascular surgery outcomes. Patients and Methods: Nine hundred eighty-three consecutive patients were divided into two groups: an early group (2012–2013) and a late group (2014–2015). The late group had received cooperatively improved perioperative wound management: our novel strategy of deep sternal infection based on radical debridement and immediate reconstruction decided by reference to severities of the patient's general condition and widespread infection by early intervention of plastic surgeons. The groups were analysed retrospectively. Binary variables were analysed statistically with the Fisher exact test and continuous variables with the Mann–Whitney U test. Inter-group differences were assessed with the chi-square test. Results: Twenty of 390 cases in the early group and 13 of 593 cases in the late group were associated with deep sternal infection. Morbidity rates of deep sternal wound infection and associated mortality rates 1 year after reconstruction surgery were significantly less ( p < 0.05 for both) in the late group. Conclusions: Intervention by plastic surgeons improved perioperative wound management outcomes. Our treatment strategy for deep sternal wound infection also reduced associated mortality rates. Facilities should consider the early inclusion of plastic surgeons in the treatment of patients undergoing aortic replacement to facilitate better outcomes.